Evaluation of Food Web Structure and Complexity in the Process of Kelp Bed Recovery Using Stable Isotope Analysis - Kim, Moon Jung; Yun, Hee Young; Shin, Kyung-Hoon; Kim, Jeong Ha (Frontiers in Marine Science, 2022)
Kelp forests have declined gradually over the world. Understanding the trophic structure of such productive and diverse ecosystems is crucial for its restoration and effective management. Few studies, however, have focused on trophic structure and functional recovery of kelp forests in the process of restoration. This study was conducted in the eastern coast of Korea where kelp bed restoration was in process with removal of sea urchins. In addition to quantitative measurement for recovery using common community parameters, we investigated how fast the stability of food web structure could be established in the newly restored kelp beds with an initially barren condition using stable isotope analysis in comparison with nearby natural bed and barren site. At the restored bed, total algal biomass and diversity reached levels of the natural bed within 1 year. While δ13C and δ15N values of macroalgae and organic matter were separated isotopically, they were similar among sites, excluding organic matter at the natural bed in 2019. Most consumers showed similar isotopic values among sites, with overlapping range for δ13C of producers. However, some herbivores showed higher δ15N values as predators/omnivore, particularly at barrens, which could be explained by trophic plasticity depending on the marcoalgal structure. In the restored bed for the first year, higher trophic diversity (CR, CD) and lower trophic redundancy (MNND, SDNND) showed non-overlapping > 50% CIs among sites. However, this distinctive stage moved toward the natural bed entering the second year as trophic diversity decreased and trophic redundancy increased while natural bed overlapped at < 50% CIS. Recovery speed in this system was fast (1 year for quantitative perspectives and 2 years for functional completion). After removing sea urchins, recruitment of macroalgae quickly increased concomitantly with consumer groups, boosting the diversity and trophic structure of the restored bed. The trophic structure of the first year of restoration was not an intermediate stage toward the completion, but a transient over-shooting state. This might have been triggered by the fast introduction of diverse macroalgae to the urchin-free space, providing an interesting finding needed to be tested in other temperate marine systems.